Refuting "Memórias de um matematiqueiro": Why _x→∞(1+1x)^x=e and not 1? - Silva, Allan Kenedy Santos (C.Q.D. - Revista Eletrônica Paulista de Matemática, 2026)
One day, in a discussion on the Discord app, one of the members of the discussion attached a link to an interview with Professor Carlos Pereira de Novaes, from UEFS, in which he claims to have developed a new algebra, which he calls ’’pseudo-real algebra’’, in which complex numbers do not exist. Still in the preface of the book where he presents his ideas, Professor de Novaes questions the limit _x→∞(1+1x)^x, stating that its value should be 1, and not e=2.71828.... In this article I propose to answer his question and explain the reason for the discrepancy between the numerical results presented in the calculation of the expression for large values ​​of x and the theoretical value e.